The active turn in Danish welfare policy:: Employment and Social Protection in Denmark - Abrahamson, Peter (SER Social, 2010)
Flexicurity is viewed as the best way of securing both a good investment environment and a secure workforce. Flexicurity combines a flexible labor market, where employers have few or no restrictions with regard to firing workers, with generous welfare benefits; and the two are facilitated through active labor market policies. Denmark really has a flexible labor market; but benefits in case of unemployment and activation cannot be described as generous in a European context. Activation is often perceived as a punishment for being unemployed and has mainly been undertaken because it is mandatory, and one is in risk of losing benefits if one refuses an activation offer. There is a price to be paid for a high degree of flexibility, and it comes in the form of marginalization and exclusion. 25 percent of the Danish population of working ages is for long spells or permanently existing on not very generous benefits outside the labor market.